Corporate Social Responsibility Activities in Arts: Focusing on Performing Production Firms in South Korea - Kang, HanYi; Shin, Hyung-Deok; Park, Jihyon (Organizations and Markets in Emerging Economies, 2023)
The purpose of this study was to investigate CSR activities in the field of arts and culture in South Korea. This study focused on government-driven CSR activities in performing arts production companies. The study collected 425 theater performance data samples from the 2015 Daehak-ro Culture Map Directory published by the Seoul Theater Center to examine which characteristics of performing arts production companies influence participation in the Nanum Ticket Program. Logistic regression analyses were performed with this data to test the hypotheses. After controlling several conditions, we found that the size of the production firm and the genre of the performance had significant effects on donation activities. In this study, the field of CSR empirical research in arts and cultural management was expanded by considering performing arts production companies as subjects of social contribution activities. This study also presents policy implications for expanding CSR activities in the field of arts and culture.
Keywords: corporate social responsibility activities; participation motivations; arts and cultural management; performing arts production companies; Nanum ticket